The notion of dyadic morality explains the logic of Zande witchcraft. Issue 2 (3rd April 2021) - Annus, Amar
ABSTRACT: The Zande witchcraft doctrine described by Evans-Pritchard is analyzed from the viewpoint of dyadic morality. Recent experimental surveys conducted in social psychology have posited a two-factor structure of mind perception in folk psychology consisting of agency and experience. The complementarity of the roles of moral agents and patients explains the automatic tendency to complete moral situations dyadically by finding agents whenever a moral patient is identified and vice versa. According to Zande customs, a person who has experienced a negative event regards oneself as a moral patient who subsequently completes the template by finding an agent. The mutual exclusivity of the perceptions of moral agency and patiency explains why Azande believe that witchcraft cannot make people break moral rules—to lie, to steal, to commit adultery, and to break taboos. The close association of witchcraft with harm perception and morality explains why people who behave immorally are more often accused of witchcraft. The Azande perceive children and animals as incapable of witchcraft because of their limited agency. Dyadic morality further explains why all male members of a clan cannot be witches. The moral typecasting theory elucidates why witches are conceived as having enhanced agency while being less vulnerable to harm.